2021
DOI: 10.1177/23779608211035845
|View full text |Cite
|
Sign up to set email alerts
|

What Helps, What Hinders? Undergraduate Nursing Students’ Perceptions of Clinical Placements Based on a Thematic Synthesis of Literature

Abstract: Introduction Clinical placements are a mandatory component of nursing students’ education internationally. Despite clinical education being a key to nursing students’ achievement of nursing competencies, few studies have reviewed students’ narratives to describe their experiences of learning during clinical placement. Such studies may be important in offering a deeper insight into clinical learning experiences than quantitative surveys. Methods A systematic thematic synthesis of qualitative studies between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
(117 reference statements)
0
14
0
Order By: Relevance
“…2021; Singh 2020), our intervention could provide valuable insights for those wishing to increase mental health knowledge of clinical facilitators and preceptors, or to assist them to identify appropriate pathways to provide support to students in preparation for clinical learning (Cant et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2021; Singh 2020), our intervention could provide valuable insights for those wishing to increase mental health knowledge of clinical facilitators and preceptors, or to assist them to identify appropriate pathways to provide support to students in preparation for clinical learning (Cant et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding self-care interventions, Moscaritolo (2009) suggested nursing students could benefit from learning mindfulness techniques in preparation for clinical learning experiences. Recent reviews have recommended students learn, and practice, positive thinking and self-affirmations before the clinical placement (Cant et al 2021) after several nursing students reported the strategies assisted them to cope more effectively with their anxiety during clinical learning (Sun et al 2020). Emerging works recommend universities better prepare nursing academics, and students for their clinical learning experiences by introducing them to well-being and anxiety management strategies such as the notion of regular practice of selfcare activities (Cleary et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…7 Students believed that a lack of supervision and not being included were factors that negatively impacted their learning. [8][9][10] An Australian qualitative study exploring student clinical learning experiences found students felt clinical learning was stressful because it is unpredictable, and they needed to be included to learn. 8 A separate Australian study further added students were bewildered and confused by university teaching and what eventuates in supervisory practice.…”
Section: Introductionmentioning
confidence: 99%
“…9 Further, a 2021 review reported indifferent staff attitudes detracted from students' learning experiences. 10 An earlier report on the future of nursing education in Australia indicated a need for education providers, placement organisation staff and RNs supervising students, to focus on prioritising planning and preparation of staff and students for clinical placements. 11 In Australia, the Nursing and Midwifery Board Standards for Registered Nurse Practice, 12 and Code of Conduct for Nurses, 13 prescribe education elements related to RNs being prepared to educate, supervise, and assess others: Standard 3.3: "uses a lifelong learning approach for continuing professional development of self and others".…”
Section: Introductionmentioning
confidence: 99%
“…This in turn, requires teachers to provide an effective set of methods to empower students to deal with the stress during their learning process and in their future careers. Placing students in a clinical setting aims to prepare them for professional situations and to facilitate the socialisation required in their professional careers (Cant R et al, 2021). Building humane relationships in the system teacher-student as a condition and factor for establishing the behavioral model of humane treatment of the patients by these future medical professionals: in providing medical help and care; in the implementation of the preventive, promotional, pedagogical, and social functions and activities of the medical specialist (Terzieva, 2009).…”
Section: Introductionmentioning
confidence: 99%